Mixed salts of amino acids with different anions - Ghazaryan, V.V.; Fleck, M.; Petrosyan, A.M. (Journal of crystal growth, 2013)
Mixed salts of amino acids with different anions are of considerable interest from chemical and structural points of view and also as a source of new materials the properties of which can be controlled by appropriate choice of anions. Four such crystals, L-His2+·Cl−·HSO4− (P212121, Z=4), L-Arg2+·NO3−·ClO4− (δ-form, P21, Z=4), L-Arg2+·F−·NO3− (P1, Z=2), 2L-Arg2+·(F−⋯HF)·3NO3− (P212121, Z=4), have been characterized structurally and by IR and Raman spectra. The hydrogen bond between the carboxyl group and the fluoride ion (2.371(3)Å) in the structure of L-Arg2+·F−·NO3− is among the shortest known O–H⋯F type hydrogen bonds. The O–H⋯F hydrogen bond in the structure of 2L-Arg2+·(F−⋯HF)·3NO3− is even shorter (2.341(2)Å) and thus belongs to the shortest contacts among both Ο–Η⋯F and F–H⋯O types hydrogen bonds. ► Four crystalline amino acid salts with different anions have been obtained. ► Molecular and crystal structures were determined by XRD and vibrational spectroscopy. ► Very short O⋯F type H-bonds were found, two shorter than any previously known.